Clinical outcome of metformin treatment in patients of acanthosis nigricans with insulin resistance (IMC Journal of Medical Science, 2017)
Background: Acanthosis nigricans (AN) is known to be associated with obesity, insulin resistance (IR) and other systemic morbid conditions. Proper treatment modalities of AN has not been established yet. Metformin may have some therapeutic effects on AN by reducing IR. Objective of the study was to examine the effect of metformin on AN in insulin resistant cases.Methodology and Results: This prospective, controlled trial was conducted in Dermatology OPD of BIRDEM General Hospital, Dhaka from September 2012 to August 2013. All the participants of the study had clinical presentation of AN on different anatomic locations such as neck, axilla, elbow, knuckle and knee and biochemical evidence of IR. Participants were of either sex with age ranging from 18 to 80 years. Any case who had contraindications to metformin therapy were excluded. Severity of AN was examined and assessed by a quantitative scale for measuring acanthosis nigricans. After detecting IR by Homeostatic Model Assessment for Insulin Resistance (HOMA-IR), cases and controls were selected by random sampling method. Randomization was done for metformin in ratio of 2:1. Every third patient was a control. Forty study participants were assigned to receive tablet metformin 500mg thrice daily after meal for three months and twenty control participants were continued on their existing therapy. To maintain a static metabolic status, patients were allowed to remain with their previous diet and lifestyle habit. After 3 months of metformin therapy, improvement was assessed and was compared with control group.Mean age of the participants in case of male: 19.75±2.36 and in case of female: 26.58±9.38, M:F= 1:14, BMI of male: 32.15±4.15 and female: 33.18± 8.05. Mean baseline neck severity score of AN: 3.57 ± 0.78 and after metformin therapy: 2.65 ± 1.02, t-test value: 4.53. Baseline neck texture score of AN: 1.87±0.80, after metformin therapy: 1.25 ± 0.86, ttest value: 3.30. Baseline AN on axilla: 3.05 ± 0.94, after metformin therapy: 2.10 ± 0.98, ttest value: 4.56. Significant improvement of AN was observed clinically on neck and axilla (P